The predictive role of endothelial glycocalyx in primary prevention of cardiovascular events:a 6 year follow-up study. (25th November 2020) - Ikonomidis, I; Thymis, J; Katsanos, S; Kousathana, F; Varoudi, M; Triantafyllou, C; Kostelli, G; Triantafyllidi, H; Lambadiari, V; Papadavid, E; Plotas, P; Tsilivarakis, D; et al.
Abstract: Introduction: Endothelial glycocalyx is a layer of glycoproteins on endothelial cells preventing vascular wall permeability to circulating proteins and blood cells. Perfused Boundary Region (PBR) of arterial microvessel is a non-invasive marker of endothelial glycocalyx thickness, as increased PBR indicates a reduced endothelial glycocalyx thickness. Cardiovasular risk factors and cardiovascular diseases have been associated with impaired PBR. However, PBR has not been studied as a predictor of major adverse cardiovascular events (MACE) in primary prevention. Methods: We studied 400 adults, without history cardiovascular disease. We measured PBR of sublingual vessels with diameter 5–25μm by GlycoCheck Software using a dedicated camera (Sidefield Darkview Imaging, Microscan MV, Nederlands). We recorded a full medical history for each subject. The participants were followed up for a period of 6 years for major cardiovascular events (including Acute Coronary Syndrome, Stroke, decompensated acute heart failure, cardiovascular death and death of all causes). Results: The mean age of participants was 49±10 years, 52% were males, 65% active smokers, 33.3% had hyperlipidemia, 12.8% type 2 Diabetes respectively, 30% hypertension and 20.5% had positive family history of premature coronary artery disease. The median PBR value was equal to 1.15 μm. After 6 years of follow up, 42 MACE were recorded (7 cardiovascular deaths). In univariate analysis, subjects with PBR values >1.15μm had greater risk of adverse events compared with those that had lower PBR (relative risk RR=2.83, p<0.05). Diabetes and hypertension were also univariate predictors of MACE (RR=3.71 and RR=2.51, p<0.05). In multivariate analysis after adjusting for atherosclerotic risk factors including diabetes and hypertension, PBR remained a an independent predictor of MACE (RR=2.67, p<0.05) Conclusion: Endothelial glycocalyx thickness appears to be an important independent predictor of adverse cardiovascular outcomes. Funding Acknowledgement: Type of funding source: None